Comparison of Scalp ERP to Faces in Macaques and Humans - Orczyk, John; Schroeder, Charles E.; Abeles, Ilana Y.; Gomez-Ramirez, Manuel; Butler, Pamela D.; Kajikawa, Yoshinao (Frontiers in Systems Neuroscience, 2021)
Face recognition is an essential activity of social living, common to many primate species. Underlying processes in the brain have been investigated using various techniques and compared between species. Functional imaging studies have shown face-selective cortical regions and their degree of correspondence across species. However, the temporal dynamics of face processing, particularly processing speed, are likely different between them. Across sensory modalities activation of primary sensory cortices in macaque monkeys occurs at about 3/5 the latency of corresponding activation in humans, though this human simian difference may diminish or disappear in higher cortical regions. We recorded scalp event-related potentials (ERPs) to presentation of faces in macaques and estimated the peak latency of ERP components. Comparisons of latencies between macaques (112 ms) and humans (192 ms) suggested that the 3:5 ratio could be preserved in higher cognitive regions of face processing between those species.